A rare case of a migrated foreign body found in and around the urinary bladder and urethra - Aditya Yelikar (MGM Journal of Medical Sciences)
Common causes of intravesical or intraurethral foreign bodies include iatrogenic injuries, self-insertion, sexual abuse, assault, and migration from adjacent sites. A 64-year-old man had been presented with a 1-year history of intermittent urinary dribbling, accompanied by painful urination (dysuria), occasional blood in the urine (hematuria), and lower urinary tract symptoms. Initially, we performed cystolithotripsy to free a guide wire encased in tissue. However, the wire remained lodged in the urinary bladder, prompting us to conduct a laparoscopic cystolithotomy for complete removal. It is possible that the guide wire either slipped into the femoral vein and was subsequently forgotten, later migrating to the urinary bladder, or that it was used to railroad a Foley catheter, which slipped into the bladder and was left behind. Foreign bodies in the urinary bladder are relatively common and should be considered when symptoms and test results are inconsistent. When endoscopic removal is not feasible, laparoscopic removal is an effective minimally invasive option.